Surface Morphological Studies of Solar Absorber Layer Cu2ZnSnS4 (CZTS) Thin Films by Non-vacuum Deposition Methods - Chandra Sekhar Kanuru; G.L. Shekar; L. Krishnamurthy; R. Gopal Krishne Urs (Журнал нано- та електронної фізики)
The consumption of fossil fuel globally has been enormous and has reached an alarming rate resulting in fast depletion of the available resources and at the same time polluting the environment. Hence there is a growing need to take cognizance of abundant amount of inexpensive energy available in the nature especially solar energy. Development and commercialization of Photovoltaics has been in focus due to its low cost, high absorption coefficient and suitable direct band gap for solar energy conversion applications. An attempt has been made in this work to synthesize the CZTS thin films by Electro deposition and Sol-gel method on Indium Tin Oxide (ITO) glass and Soda Lime Glass( SLG) substrates respectively. CZTS thin films have been prepared using a 3-stage electro chemical system wherein the precursors are deposited using platinum foil as a counter electrode and AgCl electrode as a reference electrode and Sol gel method. Surface morphology and optical properties have been studied using Atomic Force Microscopy, Scanning Electron Microscopy, X-ray Diffractometer and UV-Vis Spectroscopy